1967
DOI: 10.1063/1.1710069
|View full text |Cite
|
Sign up to set email alerts
|

LSA Oscillator-Diode Theory

Abstract: of some of the contacts. This has not as yet been investigated further.In summary, evaporated metallic contacts (Mg, In, Au, Pd, Pt) have been made to conducting strontium titanate single crystals and measurements of the electrical properties of the contacts were carried out with the following results:(1) The electrical properties of the contacts are different for the different contact metals.(2) The low-work-function metals (Mg and In) form low-resistance contacts. JOURNAL OF APPLIED PHYSICS(3) The high-work-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…2, Chapter XVI]. Later, amplitude death was observed in electronic systems [22,23] and chemical oscillators [24], causing renewed interest in this area. A theoretical analysis was given in [25], which considered a pair of linearly coupled oscillators each of which is near a Hopf bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…2, Chapter XVI]. Later, amplitude death was observed in electronic systems [22,23] and chemical oscillators [24], causing renewed interest in this area. A theoretical analysis was given in [25], which considered a pair of linearly coupled oscillators each of which is near a Hopf bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…This effect in SLs is similar to the so-called limited space-charge accumulation ͑LSA͒ mode of operation known in semiconductor devices with hot electrons. [21][22][23] The finding 20 can potentially be used for the construction of a terahertz amplifier with a large offset. However, to realize the terahertz oscillator, it is still necessary to understand how to avoid the destructive electric domains at small amplitudes in order to reach the large-amplitude regime supporting the stable operation of the device.…”
Section: Introductionmentioning
confidence: 99%
“…From the discovery of Gunn effect, it has been widely accepted that the ability to convert DC power into AC power comes from the negative effect existed in Gunn diode [12,13].The AC power is induced by the periodic motion of electronic domains in the device with a fundamental frequency the same with reciprocal of electronic domains period. Earlier simulations by drift-diffusion model have shown that when electronic domain arrives at device anode, current will reach a maximum value [12].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier simulations by drift-diffusion model have shown that when electronic domain arrives at device anode, current will reach a maximum value [12]. From then on, this concept has been widely accepted in subsequent research and teaching materials [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%